441 EFFECTS OF TRANSCATHETER AORTIC VALVE IMPLANTATION ON RENAL FUNCTION IN CT-DEFINED SARCOPENIC PATIENTS. (15th December 2022) - Ruzzarin, Alessandro; Bonatti, Matteo; Pernter, Patrizia; Engl, Patrick; Pescoller, Felix; Pesarini, Gabriele; Ribichini, Flavio Luciano; Donazzan, Luca
Abstract: Introduction: Sarcopaenia, the age-associated decline in skeletal muscle and function, increases the risk of procedure-related complications and mortality in patients undergoing transcatheter aortic valve implantation (TAVI). We sought to investigate whether CT-determined sarcopenia impacts on in-hospital renal function and on midterm outcomes following TAVI. Methods: This was a retrospective cohort study including patients who underwent TAVI. Sarcopaenia was CT-defined as skeletal muscle mass index <55.4 cm 2 /m 2 in males and <38.9 cm 2 /m 2 in females at the level of L3 vertebra. Acute kidney injury (AKI) was defined as an increase in creatinine concentration of at least 0.3 mg/dL within 48 hours of TAVI according to Valve Academic Research Consortium-3 Criteria. Acute kidney recovery (AKR) was determined as an increase of 25% in eGFR within 48 hours following TAVI. The primary endpoint was freedom from major adverse cardiac and cerebrovascular events (MACCE; composite of any cause of death, any coronary revascularization, stroke and heart failure hospitalization) at the 1-year follow up in sarcopaenic and non-sarcopaenic patients. Results: A total of 113 patients (mean age 82.2 ± 4.03 years, 52.2% female) were followed for a median of 1.1 year. Sarcopenia was found in the 59% of the TAVI population, more frequently among males (72.2% versus 33.8%, p<0.01). The incidence of AKI was 8.0% and AKR was 6.9% without differences between sarcopaenic and non-sarcopaenic patients (9.4% versus 6.5%, p=0.59 and 11.6% versus 2.2%, p=0.08). The freedom from MACCE at 1 year follow up was 74.5% for sarcopaenic and 70.3% for non-sarcopaenic patients (p= 0.6). In sarcopaenic patients, the incidence of AKI and AKR had no significant impact on the freedom from MACCE at 1-year (p=0.58 and p=0.87). Conclusions: Sarcopaenic patients had similar out of hospital incidence of adverse events to non-sarcopaenic patients following TAVI confirming the safety of this procedure in sarcopaenic patients.